Vanishing Green and the Loss of Iraq's Ecological Balance Due to Urban Expansion: Menghilangnya Lahan Hijau dan Hilangnya Keseimbangan Ekologi Irak Akibat Perluasan Kota - Ahmed Abbas Kadhim; Laith Zaid Abbas (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of rapid urbanization on the green spaces of Baghdad, highlighting the environmental, economic, and social challenges posed by unplanned urban sprawl in developing countries. Using historical and descriptive methodologies, along with comparative analysis of urban growth, the research reveals that increased migration and weak governmental oversight have significantly reduced green areas, transforming potential parks into residential and commercial zones. The findings underscore the need for stringent urban planning and policy reforms to preserve and expand green spaces, aligning with global sustainability standards to enhance urban quality of life and ecological balance in Baghdad. Highlights: Urban Expansion: Baghdad's rapid growth has significantly reduced its green spaces. Weak Oversight: Lack of strict regulations has led to the conversion of green areas into urban developments. Sustainability Strategies: Urges policy reforms and sustainable planning to enhance urban green spaces. Keywords: Urbanization, Basic Design, Green Spaces, Overpopulation, Land Use